Skip to main content
Solve for x
Tick mark Image
Graph

Similar Problems from Web Search

Share

a+b=-8 ab=-3\times 16=-48
To solve the equation, factor the left hand side by grouping. First, left hand side needs to be rewritten as -3x^{2}+ax+bx+16. To find a and b, set up a system to be solved.
1,-48 2,-24 3,-16 4,-12 6,-8
Since ab is negative, a and b have the opposite signs. Since a+b is negative, the negative number has greater absolute value than the positive. List all such integer pairs that give product -48.
1-48=-47 2-24=-22 3-16=-13 4-12=-8 6-8=-2
Calculate the sum for each pair.
a=4 b=-12
The solution is the pair that gives sum -8.
\left(-3x^{2}+4x\right)+\left(-12x+16\right)
Rewrite -3x^{2}-8x+16 as \left(-3x^{2}+4x\right)+\left(-12x+16\right).
-x\left(3x-4\right)-4\left(3x-4\right)
Factor out -x in the first and -4 in the second group.
\left(3x-4\right)\left(-x-4\right)
Factor out common term 3x-4 by using distributive property.
x=\frac{4}{3} x=-4
To find equation solutions, solve 3x-4=0 and -x-4=0.
-3x^{2}-8x+16=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-8\right)±\sqrt{\left(-8\right)^{2}-4\left(-3\right)\times 16}}{2\left(-3\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -3 for a, -8 for b, and 16 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-8\right)±\sqrt{64-4\left(-3\right)\times 16}}{2\left(-3\right)}
Square -8.
x=\frac{-\left(-8\right)±\sqrt{64+12\times 16}}{2\left(-3\right)}
Multiply -4 times -3.
x=\frac{-\left(-8\right)±\sqrt{64+192}}{2\left(-3\right)}
Multiply 12 times 16.
x=\frac{-\left(-8\right)±\sqrt{256}}{2\left(-3\right)}
Add 64 to 192.
x=\frac{-\left(-8\right)±16}{2\left(-3\right)}
Take the square root of 256.
x=\frac{8±16}{2\left(-3\right)}
The opposite of -8 is 8.
x=\frac{8±16}{-6}
Multiply 2 times -3.
x=\frac{24}{-6}
Now solve the equation x=\frac{8±16}{-6} when ± is plus. Add 8 to 16.
x=-4
Divide 24 by -6.
x=-\frac{8}{-6}
Now solve the equation x=\frac{8±16}{-6} when ± is minus. Subtract 16 from 8.
x=\frac{4}{3}
Reduce the fraction \frac{-8}{-6} to lowest terms by extracting and canceling out 2.
x=-4 x=\frac{4}{3}
The equation is now solved.
-3x^{2}-8x+16=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
-3x^{2}-8x+16-16=-16
Subtract 16 from both sides of the equation.
-3x^{2}-8x=-16
Subtracting 16 from itself leaves 0.
\frac{-3x^{2}-8x}{-3}=-\frac{16}{-3}
Divide both sides by -3.
x^{2}+\left(-\frac{8}{-3}\right)x=-\frac{16}{-3}
Dividing by -3 undoes the multiplication by -3.
x^{2}+\frac{8}{3}x=-\frac{16}{-3}
Divide -8 by -3.
x^{2}+\frac{8}{3}x=\frac{16}{3}
Divide -16 by -3.
x^{2}+\frac{8}{3}x+\left(\frac{4}{3}\right)^{2}=\frac{16}{3}+\left(\frac{4}{3}\right)^{2}
Divide \frac{8}{3}, the coefficient of the x term, by 2 to get \frac{4}{3}. Then add the square of \frac{4}{3} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{8}{3}x+\frac{16}{9}=\frac{16}{3}+\frac{16}{9}
Square \frac{4}{3} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{8}{3}x+\frac{16}{9}=\frac{64}{9}
Add \frac{16}{3} to \frac{16}{9} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{4}{3}\right)^{2}=\frac{64}{9}
Factor x^{2}+\frac{8}{3}x+\frac{16}{9}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{4}{3}\right)^{2}}=\sqrt{\frac{64}{9}}
Take the square root of both sides of the equation.
x+\frac{4}{3}=\frac{8}{3} x+\frac{4}{3}=-\frac{8}{3}
Simplify.
x=\frac{4}{3} x=-4
Subtract \frac{4}{3} from both sides of the equation.